2013
DOI: 10.1108/amhid-03-2013-0023
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behaviour therapy with a woman in her twenties with a mild intellectual disability presenting with psychogenic non‐epileptic seizures

Abstract: Purpose -This case report aims to describe the treatment of a woman (Rachel) in her twenties who was referred to the community team for people with an intellectual disability by her neurologist as she wanted help with reducing the frequency of psychogenic non-epileptic seizures (PNES). Design/methodology/approach -CBT was used as the therapeutic approach. The first stage of intervention focussed on reducing the frequency of PNES through relaxation and distraction techniques. Graded exposure was then used to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…Consideration of developmental level was reported in 15 out of 23 studies. Studies included information on adaptive skills (Atnas & Lippold, ), receptive language ability (Rose, O'Brien, & Rose, ) and assessment of the cognitive skills necessary to undertake CBT (Bishop & Henry, ). Studies considered developmental level when selecting outcome measures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consideration of developmental level was reported in 15 out of 23 studies. Studies included information on adaptive skills (Atnas & Lippold, ), receptive language ability (Rose, O'Brien, & Rose, ) and assessment of the cognitive skills necessary to undertake CBT (Bishop & Henry, ). Studies considered developmental level when selecting outcome measures.…”
Section: Resultsmentioning
confidence: 99%
“…Using the clients own language was reported by Kirkland (). Studies also reported simplification of written and verbal language, for example by using accessible information sheets (Atnas & Lippold, ; Wright, ) and reducing the need for written psycho‐educational materials (Kellett et al., ). Studies also noted the need for specific questions at times (Hurley, ), as well as the need for simple words and short sentences (Willner & Goodey, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the authors' knowledge, there is only one published case study describing the use of CBT to treat PNES in an individual with ID (Atnas and Lippold, 2013). Atnas and Lippold based their intervention on the CBT treatment protocol for PNES outlined by Goldstein et al (2004), with the client experiencing a reduction in the number of seizures by the end of the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is no literature describing the delivery of a CBT-based intervention adapted for individuals with ID that involves caregivers in the treatment of PNES. It will also describe an adapted approach to the cognitive restructuring element of Goldstein et al's (2004) protocol, not included in Atnas and Lippold's (2013) case report. Given the success of CBT to treat PNES in the general population, it is important to further develop the literature describing how evidence-based treatment protocols for PNES can be adapted for individuals with ID and to help provide a framework to approach treatment in this significant population of patients presenting with PNES.…”
Section: Introductionmentioning
confidence: 99%